Pengaruh Beban Kerja, Kelelahan Kerja Dan Work Family Conflict Terhadap Stres Kerja Wanita Buruh Tani di Desa Tubanan, Kec. Kembang - nurmalasari, febriana (JEBIM Prima, 2023)
Abstract A farm laborer is someone who works on someone else's land to get produce or wages from the land owner. This study aims to determine the effect of workload, work fatigue and work family conflict on the work stress of female farm workers in Tubanan Village, Kec. flower This research is a study using a quantitative approach to the survey method of respondents. The subjects involved in this study were women farm workers in Tubanan Village, Kec. Flower which totaled 76 respondents by means of multiple linear regression model analysis. The collection of technical data in this study used the SPSS software program. Based on the results obtained, the factors that influence work stress are work family conflict. This is evidenced by the results of hypothesis testing which shows a sig value of less than 0.05, which is equal to 0.008. While workload has no effect on work stress seen from a sig value greater than 0.05, which is equal to 0.054. Work fatigue has no effect on work stress seen from a sig value greater than 0.05, which is equal to 0.192.Keywords:Workload, Work Fatigue, Work Family Conflict, Work Stress